1990
DOI: 10.1002/jemt.1060140207
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular processing of endocytosed proteins

Abstract: In conclusion, proteins of hepatobiliary transport utilize receptor-mediated endocytosis and intracellular vesicles and rely on functionally dynamic microtubules for their transport by hepatocytes. The many diverse transport pathways in hepatocytes reflect the many functions served by the uptake of various proteins from the blood. The mechanisms of sorting of ligands and their receptors in endosomes and the factors that regulate the intracellular transport pathways are not yet known. Future investigations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Mechanisms of Protein Disposition Soluble material, such as lipid particles, im mune complexes, bacterial toxins, certain lyso somal enzymes as well as denatured or other wise abnormal glycoproteins, can be handled by the liver by a versatile apparatus for recep tor-mediated uptake and degradation [114], Endocytosis is not specific for the liver cells but occurs in all eukaryotic cells except mature red blood cells [2,67,97,115,116], At least three different endocytotic mech anisms can be involved in the interiorization of such materials [67,97], Acinar Heterogeneity in Uptake For a number of compounds such as ga lactose [70], parathion [27,28] and paraoxon [113], acinar gradients are observed in nor mal perfusions. Since no further data are available, this heterogeneous involvement cannot yet be ascribed to intrinsic differ (1) Fluid phase endocytosis or pinocytosis is a nonsaturable engulfment process that does not require membrane binding.…”
Section: Endocytosis Of Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mechanisms of Protein Disposition Soluble material, such as lipid particles, im mune complexes, bacterial toxins, certain lyso somal enzymes as well as denatured or other wise abnormal glycoproteins, can be handled by the liver by a versatile apparatus for recep tor-mediated uptake and degradation [114], Endocytosis is not specific for the liver cells but occurs in all eukaryotic cells except mature red blood cells [2,67,97,115,116], At least three different endocytotic mech anisms can be involved in the interiorization of such materials [67,97], Acinar Heterogeneity in Uptake For a number of compounds such as ga lactose [70], parathion [27,28] and paraoxon [113], acinar gradients are observed in nor mal perfusions. Since no further data are available, this heterogeneous involvement cannot yet be ascribed to intrinsic differ (1) Fluid phase endocytosis or pinocytosis is a nonsaturable engulfment process that does not require membrane binding.…”
Section: Endocytosis Of Proteinsmentioning
confidence: 99%
“…(2) Adsorptive endocytosis or pinocytosis operates through an aspecific binding of the substrate to the membrane by which the sub strate becomes concentrated and is endocytosed more efficiently than via a fluid phase mechanism [20], (3) Receptor-mediated endocytosis in volves binding to more specific receptors [2,[114][115][116][117][118], Among the macromolecules that undergo receptor-mediated endocytosis are growth factors, hormones, transport proteins, pro teins destined for degradation such as a2-macroglobulin, proteins to be transported across polarized cells (IgA) as well as toxins and viruses. After binding of the ligand to the receptor, coated pits are formed that are internalized as coated vesicles.…”
Section: Endocytosis Of Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that in humans, the epithelial cells of biliary ductules are involved in the synthesis of the secretory component and the transport of sIgA into the bile. 12 It is believed that IgA passes through the cells by first binding to the secretory component in the basolateral side of the cell. [13][14][15] Using isolated and cultured cells, Sakisaka 16 demonstrated that labeled pIgA2 was transported transcellularly via the tubulovesicular pathways and secreted into the bile canalicular space in cultured rat hepatocytes, while it was transported via the tubulovesicular pathway and secreted into the luminal spaces in cultured guinea pig BEC.…”
Section: Immunoglobulins In Bilementioning
confidence: 99%